Inclusive education for deaf and hard-of-hearing learners in Zambia: An appraisal of the 2023 curriculum framework - Rachel Muuma Chomba (S&Co Publishing, 2026)
This study examines Zambia's 2023 Education Curriculum Framework in relation to inclusive education, with a focus on learners who are deaf or hard of hearing. Drawing on policy documents, recent academic literature, and the 2025 National Disability Policy, this study explores whether inclusive education for learners who are deaf or hard of hearing in Zambia is a policy reality or remains a distant aspiration. The findings indicate that while the 2023 Curriculum Framework promotes inclusive education at a conceptual and policy level, its provisions for learners with hearing impairments remain largely rhetorical, lacking enforceable mechanisms for linguistic accessibility, curriculum adaptation, and institutional accountability. While the curriculum and associated reforms show commitment to inclusion, gaps in implementation, teacher training, curriculum differentiation, and accessibility continue to hinder full participation for these learners. Recommendations for strengthening inclusive practices, particularly for learners who are deaf or hard of hearing, are presented.